2010
DOI: 10.1089/fpd.2010.0572
|View full text |Cite
|
Sign up to set email alerts
|

TrackingSalmonellaContamination in Various Watersheds and Phenotypic and Genotypic Diversity

Abstract: Salmonella enterica is an important foodborne pathogen, and contamination of surface and ground water that may result from various human activities, such as animal production and urbanization, may contribute to the public health burden. The aims of this study was to determine the sources of Salmonella contamination in four different types of watersheds and to assess the relative contribution of multidrug-resistant strains. Eighty-six water samples collected from four different watershed systems, including thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 19 publications
4
68
1
1
Order By: Relevance
“…Previous studies have shown the persistence of Salmonella in various ecological niches of Virginia's eastern shore agricultural region (8,(18)(19)(20). Most recently, ecological surveillance data on VES tomato farms by Bell et al (21) and Micallef et al (22) provide further evidence that Salmonella persists in the VES tomato-growing environment, particularly in pond water often used for irrigation, or in creek water that flowed downstream of the pond, pond or creek sediment, and soil.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown the persistence of Salmonella in various ecological niches of Virginia's eastern shore agricultural region (8,(18)(19)(20). Most recently, ecological surveillance data on VES tomato farms by Bell et al (21) and Micallef et al (22) provide further evidence that Salmonella persists in the VES tomato-growing environment, particularly in pond water often used for irrigation, or in creek water that flowed downstream of the pond, pond or creek sediment, and soil.…”
Section: Discussionmentioning
confidence: 98%
“…Other surveys in different regions of the United States reported a lower percentage of MDR isolates from agricultural water. For example, only one MDR isolate (serotype Miami) was isolated from agricultural water in North Carolina (45), and a survey of water samples from 14 tomato farms in mid-Atlantic coast states found only three (4.8%) MDR Salmonella strains (42). However, none of our MDR patterns overlapped with the MDR patterns in those studies, except that streptomycin resistance was widely distributed among the MDR strains in most cases, possibly due to the widespread streptomycin exposure of bacteria in soil (46).…”
Section: Figmentioning
confidence: 99%
“…A number of studies have shown that water can act as both a source of pathogens and a vehicle of pathogen introduction to preharvest environments and produce (20,(22)(23)(24)(25). For example, surface water has been reported to have a wide range of Salmonella (6% to 80%) and L. monocytogenes (6.4% to 62%) prevalence (24,(26)(27)(28)(29). In particular, Salmonella prevalence of 6 to 9% has been reported for water samples obtained from produce-growing regions in California and New York State (14,23).…”
mentioning
confidence: 99%